ANALISIS SISTEM INFORMASI AKUNTANSI PERSEDIAAN - Sofyan Mulyadi , Muhammad Fadly; Arnan , Sendi Gusnandar; Dewa Brata, Ignatius Oki ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2024)
Inventory is one of the important assets in a company's operational activities. Without good inventory management, the company is likely to be unable to meet market/consumer desires. Therefore, a well-designed inventory accounting information system is needed to provide accurate and relevant information regarding the condition of inventory in the warehouse so that it can provide useful information for management in decision making. The purpose of this study is to analyze the existing inventory accounting information system at CV Arghani and assess the performance of the inventory accounting information system at CV Arghani based on PIECES analysis and TELOS analysis. PIECES analysis shows that the AKIS system is not yet effective and accurate in presenting inventory information in the warehouse. Inaccurate stock and the absence of warehouse cards make it difficult to monitor and update stock in real time, hampering the sales process. TELOS analysis shows that, although this system is technically, economically, legally, operationally, and schedule-wise feasible, improved data back-up is needed for better data security. Overall, the performance of the current AKIS system does not support the company's operations optimally..